Comparison of Frequency of Home Births in the Member States of the EU Between 2015 and 2019 - Galková, Gabriela; Böhm, Pavel; Hon, Zdeněk; Heřman, Tomáš; Doubrava, Radan; Navrátil, Leoš (Global pediatric health, 2022)
Introduction. The disagreement of the general public's views on home births is practically identical for the professional public and specialists also. The core of the problem lies in the disunity between individual countries of the European Union-complete prohibition under the risk of committing a crime on one side and standard procedure perceived as something completely common on the other side. Methods. The authors focused on the prevalence of home births in individual EU countries, together with the proportion of neonatological mortality compared to the number of live births, which are data that, unlike home births, are mandatory in each EU Member State. Data on home births were obtained from available official and verified sources such as the Ministry of Health, reviews published by the WHO, or published peer-reviewed scientific and professional works. Secondary data were procured via Web of Science, Scopus, or PubMed. Results. The aim of the study was to trace the documented numbers of home births in the individual states of the European Union in the years 2015 to 2019, to analyze them with data on live births together and with data on infant mortality. A comparative analysis of the compiled data can be used to conclude which countries have the highest domestic birth rates and how the birth rate is manifested in these countries. Based on the analysis of available data, it can be determined that the Netherlands, Denmark, and Germany have the highest share of domestic births. The link between home births and increased neonatal mortality has not been established. Eastern Europe countries have the highest neonatal mortality, namely Romania (1.19%) and Malta (0.63%). Conclusion. The Netherlands has the highest domestic birth rate per 100 000 inhabitants with a 5-year average of 161 922 (overall average of all live births 993.40), but is also in 11th place in neonatal mortality, together with Denmark and Belgium, which have 0.35% neonatal neonatal mortality. The country with the lowest neonatal mortality of 0.19% is Slovenia. The total average of all children born in 5 years (915 live births) is 1.422. When monitoring the number of domestic births in other countries in the years 2015 to 2019, an increasing tendency of this trend is observed.
Keywords: neonatal mortality rate; home births; labor difficulties; European Union